It’s All About Eggs: Teaching Lifelong Learners - Felman, Jyl Lynn (Radical Teacher, 2017)
After thirtyfive years of teaching college the author begins a new pedagogical exploration teaching seniors in two very different programs, one, a Queer Seniors Institute and the other at an Osher Lifelong Learners Institute of primarily affluent members. Along the way she discovers a whole new style of teaching.